A Review on: Bioanayltical Method Development and Validation - Suvarna V. Pawar; Dr. Vinayak M. Gaware (Asian Journal of Pharmaceutical Research and Development, 2025)
The creation of selective, sensitive, and reliable bioanalytical methods for accurately quantifying drugs and their metabolites in biological samples is a critical component of successful drug development. These methods ensure that the analytical processes used are suitable for biomedical purposes. Bioanalytical method validation encompasses a series of procedures designed to confirm that a method employed for quantifying analytes in biological matrices like blood, plasma, serum, or urine is dependable and consistent for its intended applications.The data derived from such methods is essential for regulatory submissions, including investigational new drug applications (INDs), new drug applications (NDAs), abbreviated new drug applications (ANDAs), biologic license applications (BLAs), and their respective supplements. These validated methods play a vital role in human clinical pharmacology, bioavailability (BA), and bioequivalence (BE) studies, which require accurate evaluation of pharmacokinetic, toxicokinetic, or biomarker concentrations.Therefore, it is crucial to ensure that bioanalytical methods are carefully developed, thoroughly validated, and documented to meet the required standards, ensuring reliable results in drug analysis. High-performance liquid chromatography (HPLC) is a versatile analytical technique, particularly beneficial for identifying and quantifying low concentrations of drugs and metabolites in biological matrices. As such, developing and validating HPLC-based bioanalytical methods for low-dose drugs offers significant advantages.This article highlights advancements in HPLC-based bioanalytical method development and validation for various drugs, emphasizing their documentation and applications.